Delay Discounting is Associated with Treatment Response among Cocaine-Dependent Outpatients - Washio, Yukiko (2011)
RATIONALE: Delay discounting (DD) describes the rate at which reinforcers lose value as the temporal delay to their receipt increases. Steeper discounting has been positively associated with vulnerability to substance use disorders, including cocaine use disorders. OBJECTIVES: In the present study, we examined whether DD of hypothetical monetary reinforcers is associated with the duration of cocaine abstinence achieved among cocaine-dependent outpatients. METHODS: Participants were 36 adults who were participating in a randomized controlled trial examining the efficacy of voucher-based contingency management (CM) using low-magnitude (N = 18) or high-magnitude (N = 18) voucher monetary values. RESULTS: DD was associated with the number of continuous weeks of cocaine abstinence achieved, even after adjusting for treatment condition during the initial 12-week (t(33) = 2.48, p = .045) and entire recommended 24-week of treatment (t(33) = 2.40, p = .022). Participants who exhibited steeper discounting functions achieved shorter periods of abstinence in the Low-magnitude voucher condition (12-week: t(16) = 2.48, p = .025; 24-week: t(16) = 2.68, p = .017), but not in the High-magnitude voucher condition (12-week: t(16) = 0.51, p = .618; 24-week: t(16) = 1.08, p = .298), although the interaction between DD and treatment condition was not significant (12-week: t(32) = −1.12, p = .271; 24-week: t(32) = −0.37, p = .712). CONCLUSIONS: These results provide further evidence on associations between DD and treatment response and extend those observations to a new clinical population (i.e., cocaine-dependent outpatients), while also suggesting that a more intensive intervention like the High-magnitude CM condition may diminish this negative relationship between DD and treatment response.